2001
DOI: 10.1006/eesa.2001.2045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endosulfan and Parathion on Energy Reserves and Physiological Parameters of the Terrestrial Isopod Porcellio dilatatus

Abstract: The in vivo effects of parathion and endosulfan on the isopod Porcellio dilatatus were investigated. Feeding parameters (food consumption and assimilation rates), growth, and energy reserves (glycogen, lipid, and protein contents) of pesticide-exposed isopods were compared with those of control animals. Isopods were exposed to a wide range of concentrations of parathion or endosulfan (0.1, 1, 10, 25, 50, 100, 250, and 500 microg/g of food) for 21 days. The route of uptake of the pesticides was through the diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 27 publications
8
59
1
1
Order By: Relevance
“…The growth-inhibition rates in the treatment group of 400 mg/kg dw BDE-47 reached a maximum of 36.4 % after 14-day exposure, but no deaths appeared to occur in all treatment groups. Ribeiro et al (2001), working on isopods (Porcellio dilatatus), found that feeding inhibition decreased consumption rates and regulated the intake of the pesticide, thus resulting in decreased growth rate. This strategy of decreasing food intake to avoid toxins was introduced to explain the increasing growth inhibition of the earthworms in similar ecotoxicology tests (Bibič et al 2007;Mosleh et al 2003;Shi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The growth-inhibition rates in the treatment group of 400 mg/kg dw BDE-47 reached a maximum of 36.4 % after 14-day exposure, but no deaths appeared to occur in all treatment groups. Ribeiro et al (2001), working on isopods (Porcellio dilatatus), found that feeding inhibition decreased consumption rates and regulated the intake of the pesticide, thus resulting in decreased growth rate. This strategy of decreasing food intake to avoid toxins was introduced to explain the increasing growth inhibition of the earthworms in similar ecotoxicology tests (Bibič et al 2007;Mosleh et al 2003;Shi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the treated worms lost weights. Reduction in feeding activity as a strategy to avoid the pyridine containing pesticides was proposed to explain the weight reduction in an isopods [37]. In our case, this possibility may be ruled in and it may be proposed that T. tubifex growth rate was reduced because of a higher consummation of the reserves.…”
Section: Pyridine and Formaldehyde Toxicitymentioning
confidence: 64%
“…Box represents first quartile, median value, and third quartile decrease to approx. 1% upon starvation (van Brummelen and Stuijfzand 1993;Lavy et al 1997;Ribeiro et al 2001). So, using the latter value, internal concentrations ranged from an estimated 2.1 to 775 lg/g lipid at exposure levels between 3 and 300 mg/kg dry soil.…”
Section: Resultsmentioning
confidence: 99%